Looking for a spouse: marriage, inheritance and mutual aid in a Colca Valley district - Paerregaard, Karsten (1990)
The purpose of my article is to contribute to the development of a general model of the social organization of the Andean world, in which few have been interested in the last ten years. There are two aspects that I am going to analyze based on data collected in the Tapay district, in the Colca valley, Cailloma province, Arequipa department. First, I want to analyze the marriage pattern that characterizes on the one hand the relationship between the Tapay district and the external world, and on the other hand the relationships between the social and cultural groups that make up the Tapay population. In other words, to analyze how exogamy and endogamy are manifested in the different levels of the society of Tapay. Secondly, I will try to interpret this marriage pattern within a broader context, that of Tapay's social organization. Therefore, I will present a series of data about the inheritance system and the mutual aid amongst the people of Tapay.